Explosion limits for combustible gases - TONG, Min-ming; WU, Guo-qing; HAO, Ji-fei; DAI, Xin-lian (Mining science and technology (China), 2009)
Combustible gases in coal mines are composed of methane, hydrogen, some multi-carbon alkane gases and other gases. Based on a numerical calculation, the explosion limits of combustible gases were studied, showing that these limits are related to the concentrations of different components in the mixture. With an increase of C4H10 and C6H14, the Lower ExplosionLimit （LEL） and Upper Explosion-Limit （UEL） of a combustible gas mixture will decrease clearly. For every 0.1% increase in C4H10 and C6H14, the LEL decreases by about 0.19% and the UEL by about 0.3%. The results also prove that, by increasing the amount of H2, the UEL of a combustible gas mixture will increase considerably. If the level of HE increases by 0.1%, the UEL will increase by about 0.3%. However, H2 has only a small effect on the LEL of the combustible gas mixture. Our study provides a theoretical foundation for judging the explosion risk of an explosive gas mixture in mines.